Perilaku Religius Siswa Madrasah Ibtidaiyah: Tinjauan atas Pembiasaan Ibadah, Peran Orang Tua, Keteladanan Guru, Teman Sebaya, dan Dukungan Masyarakat - Darmawan, Didit; Umar, Hanif (Rayah Al-Islam, 2026)
This literature study aims to analyze the interaction between daily worship practices, parental role, teacher modeling, peer interaction, and community support in shaping the religious behavior of Islamic elementary school students. The method used is qualitative research with a thematic synthesis approach following a systematic literature review procedure. The data are derived from documents relevant to the study, collected using documentation techniques, and analyzed through descriptive analysis. The results indicate that consistent daily worship practices accompanied by warm parental attention establish foundational religious habits that become ingrained as character. Parental attention proves to be a primary determinant in shaping children's religious character through consistent accompaniment and the creation of a religious atmosphere at home. Teacher modeling in schools reinforces values instilled at home through visible consistency between words and actions in daily interactions. Positive peer interaction provides social reinforcement through mutual reminding and emulation mechanisms within friendship groups. Community support through the provision of worship spaces, religious activities, and collective supervision expands the arena for value internalization, enabling children to experience religion as a shared concern beyond individual obligation. The synergy between these five factors creates a robust educational ecosystem for shaping a religious generation from an early age, where each element strengthens and complements the others. This study contributes theoretically to enriching the ecological perspective on Islamic education and practically provides reflective foundations for parents, teachers, and community leaders in optimizing their respective roles in religious character formation.